Students’ Perceptions on the Use of Medium Instruction (EMI) at SMP Cahaya Bangsa Metro - Siti Shifa Alawiyah Nurul Alam; Yeni Suprihatin; Eka Yuniasih (CV. Creative Tugu Pena, 2024)
This study explores students’ perceptions and challenges in the implementation of English as a Medium of Instruction (EMI) at SMP Cahaya Bangsa Metro, Indonesia. EMI is increasingly adopted in non- English-speaking countries to prepare students for global academic and professional opportunities. The research utilized a descriptive method with purposive sampling, involving 11 eighth-grade students who had one year of EMI experience. Data were collected through classroom observation, semi-structure interviews, and documentation. Findings show that while students recognize the benefits of EMI, such as improved language proficiency and future opportunities abroad, they also face significant challenges. These challenges include difficulties with academic vocabulary, understanding technical terms, and adapting to teacher accents, particulary in subjects like science and math. Additionally, students prefer a mixed-language approach to enhance comprehension. The study higlights the need for tailored language support, clearer instructional strategies, and teacher training to address these challenges. By addressing these issues, educational institutions can create a more inclusive and effective learning environment for EMI students.